Pelatihan WhatsApp Bisnis untuk Strategi Pemasaran Pada UMKM di Teweh Tengah, Kalimantan Tengah - Fajar Rizky Hadi; Tutut Dewi Astuti (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
MSMEs play an important role towards the Golden Indonesia 2045 by utilizing the significant development of digitalization. Digitalization is used by business people to attract the attention of buyers from other regions through existing social media. In Indonesia alone, social media users reach 139 million users, the magnitude of this opportunity must be utilized by business people, especially MSMEs, so that their business develops and becomes a solid foundation for welcoming the Golden Indonesia 2045. This community service aims to help MSMEs better utilize existing technology to facilitate transactions, as well as communicate with customers. The method used is to assist MSMEs in building WhatsApp Business for their business. The results obtained are MSMEs' understanding of WhatsApp Business and better use of the application before the service is carried out, as well as the benefits obtained by MSMEs after using WhatsApp Business.